The Validity of Determining The Value of Fines In Motor Vehicle Loan Agreements That Exceeds Limitations In the law - Ignasius Tungga; Nynda Fatmawati Octarina (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
The high price of motor vehicles results in not everyone being able to buy cash, non-cash motor vehicle purchases obtained through consumer finance with the lease financing agreement procedure, even though de facto consumers control the goods, BPKB and STNK, but de yure on goods financing contracts whose credit is financed as debt collateral, which means that ownership is on the part of the financial institution. The purpose of this article is: 1) Describe the determination of the value of fines in the credit agreement. 2) Describe the Validity of the determination of penalty value in motor vehicle credit agreements that exceed the limitation in the law. This research is a qualitative normative juridical. The approach used is the statute approach. From the results of the discussion it was concluded: 1) Determination of the value of the fines in the financing credit agreement following LKPP Regulation No. 14/2012. Article 120 Perpres No. 54/2010 Jo. Perpres No. 35/2011 Jo. Perpres No. 70/2012 is 1/1000 or 0.5% of the contract value for each day of delay. 2) Inclusion of Fines in the Raw Clause is based on Article 15 (1) of the Financial Services Authority Regulation No./POJK.05/2014 Jo. Article 38 (1) 35/POJK.05/2018 as a default (negligent/alpha). While the Determination of the value of fines in the motor vehicle credit agreement that Exceeds the Limitation is legal by law as Article 1239 of the Civil Code is strengthened Article 1338, 1339 of the Civil Code.